2021
DOI: 10.1016/j.jopan.2020.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Smart Glasses for Anesthesia Care: Initial Focus Group Interviews with Specialized Health Care Professionals

Abstract: Smart glasses are a kind of wearable technology that gives users sustained, hands-free access to data and can transmit and receive information wirelessly. Earlier studies have suggested that smart glasses have the potential to improve patient safety in anesthesia care. Research regarding health care professionals' views of the potential use of smart glasses in anesthesia care is limited. The purpose of this study was to describe anesthesia health care professionals' views of smart glasses before clinical use. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Connectivity, frequent system shut-downs and restarts, and battery life caused irritation. This was also an area about which anesthesia HCPs were apprehensive before clinical use [18]. The results do not provide information about whether the technical problems NAs encountered in this study were caused by the Wi-Fi, the customized application, or by the SG as platform, or if they were a combination of the aforementioned reasons.…”
Section: Discussion Of Resultsmentioning
confidence: 73%
See 4 more Smart Citations
“…Connectivity, frequent system shut-downs and restarts, and battery life caused irritation. This was also an area about which anesthesia HCPs were apprehensive before clinical use [18]. The results do not provide information about whether the technical problems NAs encountered in this study were caused by the Wi-Fi, the customized application, or by the SG as platform, or if they were a combination of the aforementioned reasons.…”
Section: Discussion Of Resultsmentioning
confidence: 73%
“…This finding is supported by others [27,30], and the possibility to improve alarm management with SG is endorsed for future development. This feature was highlighted before clinical use in both an anesthesia- [18] and intensive care context [17]. A review of physiological monitor alarms found that between 74-99% of them were non-actionable, and an increasing number of alarms was associated with longer response time from nurses [49].…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations